Assessment of risk factors in pyogenic liver abscesses in children - Anurag Pandey; K Rajeshwari; Deepak Kumar; Garima Gupta (Wolters Kluwer Medknow Publications, 2023)
Background: Pyogenic liver abscess (LA) is a significant contributor to morbidity and mortality in developing countries like India. The risk factors predisposing to the LA specifically in children are not known. Studies done in the past largely remain inconclusive and have identified only probable causes. The cause of LA in children with no coexisting illness remains unknown. Methodology: This prospective observational study was conducted at a tertiary teaching hospital located in New Delhi, India. All children between 2 months and 12 years of age with sonographically confirmed LA presenting to the hospital were included and managed with appropriate intravenous antibiotics and relevant investigations. Results: A total of 52 children were included. The mean age was 6 years and 4 months, and the male: female ratio was 1.4:1. Around 50% of the patients were malnourished. Fever, abdominal pain and loss of appetite were the most common symptoms. Nine patients (17%) were managed conservatively, 13 (25%) needed percutaneous needle aspiration and 30 (57.69%) required drainage using a pigtail catheter. Poor socioeconomic status and anaemia were found to be the most commonly associated risk factors. Selective immunoglobulin A (IgA) deficiency was the most common primary immunodeficiency disorder followed by T-cell defect. On multivariate analysis, it was seen that in those with clinical icterus, gamma-glutamyl transferases >350 IU/m, and those with impending rupture, the time to defervescence was significantly different (P = 0.05). Conclusion: Poor socioeconomic status causing malnutrition emerged as a significant risk factor for LA in children. Selective IgA deficiency was the most common immunodeficiency seen in a few children. Adopting a conservative approach like aspiration and percutaneous drainage led to lower mortality and good recovery rates.